ATHLOS Healthy Aging Scale score as the predictor of all-cause mortality in Poland and Czechia - Kozela, Magdalena; Pająk, Andrzej; Szafraniec, Krystyna; Ayuso-Mateos, José Luis; Bobak, Martin; Lu, Wentian; Pikhart, Hynek; Polak, Maciej; Sanchez-Niubo, Albert; Stepaniak, Urszula; Haro, Josep Maria (Frontiers in Public Health, 2023)
Background: The ATHLOS consortium (Ageing Trajectories of Health–Longitudinal Opportunities and Synergies) used data from several ageing cohorts to develop a novel scale measuring healthy ageing comprehensively and globally (ATHLOS Healthy Ageing Scale). In the present study, we assessed the predictive performance of the ATHLOS Healthy Ageing Scale for all-cause mortality in middle aged and older adults. Methods: Data from the Polish and Czech HAPIEE (Health Alcohol and Psychosocial factors In Eastern Europe) prospective cohorts were used. There were 10,728 Poles and 8,857 Czechs recruited. The ATHLOS Healthy Ageing Scale score was calculated for all participants using data form the baseline examination carried out in 2002-05. The follow up for all-cause mortality was completed for 14 years. The associations between quintiles of the ATHLOS Healthy Ageing Scale and all-cause mortality were estimated using Cox proportional hazards models. Results: A total of 9,922 Polish and 8,518 Czech participants had data on the ATHLOS Healthy Ageing Scale and mortality (with 1828 and 1700 deaths, respectively). After controlling for age, the ATHLOS Healthy Ageing Scale score was strongly associated with mortality in graded fashion in both genders and countries (hazard ratios for lowest vs. highest quintile were 2.98 and 1.96 in Czech and Polish women and 2.83 and 2.66 in Czech and Polish men, respectively). The associations were only modestly attenuated by controlling for education, economic activity and smoking, and there was further modest attenuation after additional adjustment for self-rated health. Conclusion: The novel ATHLOS Healthy Ageing Scale is a good predictor of all-cause mortality in Central European urban populations, suggesting that this comprehensive measure is a useful tool for assessment of future health trajectories of older persons.